Evidence for Low‐Temperature Diffuse Venting at North Pond, Western Flank of the Mid‐Atlantic Ridge. (5th June 2019) - Villinger, H. W.; Müller, P.; Bach, W.; Becker, K.; Orcutt, B. N.; Kaul, N.; Wheat, C. G.
Abstract: During expedition MSM37 on the German RV Maria S. Merian, bottom water temperature and sediment temperature profiles were measured in the vicinity of North Pond (western flank of Mid‐Atlantic Ridge) during exploratory dives with Remotely Operated Vehicle Jason II. In addition, push cores were taken at locations with high sediment temperature gradients. We could identify two locations where sediment temperature gradients exceed 1 K/m and bottom water temperatures showed an anomaly of up to 0.04 °C above background. We interpret these observations as clear indication of low‐temperature diffuse venting of fluids that have traveled through the uppermost crust. We can safely assume that the observed phenomena are widespread at ridge flank settings where sediment cover is thin or absent, and hence, we can explain the efficient heat mining on ridge flanks. Due to the difficulties of locating diffuse low‐temperature discharge sites and due to the fact that discharge can occur through thin sediment cover as well as through sediment‐free basement outcrops, it will be very difficult to quantify fluxes of energy and mass from low‐temperature diffuse venting in ridge flank settings; however, thermal anomalies may be used to locate sites of discharge for geochemical, microbial, and hydrologic characterization. Plain Language Summary: Similar to the movement of groundwater in continental aquifers, the circulation of seawater in the rocky oceanic crust below the seafloor transports about 25% of Earths global heat loss. Although the well‐known hydrothermal vents along the mid‐ocean ridges also transport heat from the Earths interior, the majority of heat loss occurs on the flanks of mid‐ocean ridges at much lower temperatures. Finding sites where these minimally heated fluids escape the seafloor is challenging, due to the subtle differences compared to the ambient conditions at the seafloor. Building on decades of studies on the western flank of the Mid‐Atlantic Ridge, this study used high‐resolution temperature profiles from shallow sediment layers over oceanic crust, combined with anomalies in bottom seawater temperatures, to locate spots where subtly warmed hydrothermal fluids diffuse out of the seabed. Finding these locations is the first step for further determining how much energy and mass changes during seawater circulation below the seafloor. Key Points: Exploratory dives with ROV Jason II around North Pond (MAR) were used for extensive sediment temperature measurements Some locations with thin sediment cover show anomalously high temperature gradients At two sites high temperature gradients are associated with bottom water temperature anomalies